Fabrication, microstructural and mechanical behavior of Al-Al2O3-SiC hybrid metal matrix composites. (2020) - Hossain, Shakil; Mamunur Rahman, MD; Chawla, Devesh; Kumar, Alip; Seth, Prem Prakash; Gupta, Pallav; Kumar, Devendra; Agrawal, Rajeev; Jamwal, Anbesh
Abstract: In this present study aluminium-based, hybrid metal matrix composite is developed by stir casting method. Al2 O3 content is fixed as 1 wt% and SiC content is varied from (0, 2, 4, 6, and 8) wt.% as reinforcement materials. Microstructure, mechanical properties and wear behaviour of prepared samples have been investigated. The result indicates that incorporation of Al2 O3 and SiC reinforcements in aluminium Al-6103 grade matrix improved hardness and wear resistance of the material. 8 wt% SiC and 1 wt% of Al2 O3 reinforced AMCs shows maximum hardness. Optical micrographs show the uniform dispersion of SiC and Al2 O3 particles within the aluminium matrix. It is expected that this composite will be beneficial for lightweight material development especially in marine engineering applications.